2008
DOI: 10.1177/1088357607311443
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Joint Attention and Language in Children With Autism Spectrum Disorders

Abstract: The relationship between initiation of and response to joint attention and components of receptive and expressive language in 20 children with autism between the ages of 3 and 5 years were examined. Receptive language skills were assessed using the Mullen Scales of Early Learning (MSEL). Expressive language skills were evaluated by examining Mean Length of Utterance and Type Token Ratio. These variables, along with data on responses to joint attention bids and initiation of joint attention were analyzed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
42
2
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 34 publications
6
42
2
4
Order By: Relevance
“…Considering the relationship between joint attention skills and language skills, the findings were in line with previous reports, in that language abilities were related to RJA skills, but not to IJA skills (Murray et al, 2008). Although a significant correlation was found between RJA and IJA skills, this finding suggests that both joint attention skills also rely on distinct processes.…”
Section: Initiation Of Joint Attention Skillssupporting
confidence: 90%
See 1 more Smart Citation
“…Considering the relationship between joint attention skills and language skills, the findings were in line with previous reports, in that language abilities were related to RJA skills, but not to IJA skills (Murray et al, 2008). Although a significant correlation was found between RJA and IJA skills, this finding suggests that both joint attention skills also rely on distinct processes.…”
Section: Initiation Of Joint Attention Skillssupporting
confidence: 90%
“…Even after controlling for mental age, a significant correlation was found between RJA and IJA skills (on a lower level). However, there are also studies with children with ASD which report nonsignificant correlations between RJA and IJA skills (e.g., Kasari, Paparella, & Freeman, 2008;Murray et al, 2008). The children with ASD in these studies were somewhat older than the children in our study, but the contradictory findings may rather be due to differences in the methods used.…”
Section: Initiation Of Joint Attention Skillscontrasting
confidence: 72%
“…The association of IJA and receptive language is in line with Charman et al (2003). However, several other studies that included IJA and RJA, found a unique association between RJA and receptive language, and no association between IJA and language in general (Luyster et al, 2008;Murray et al, 2008;Thurm et al, 2007). Part of the children in these studies had a language age higher than 2 years old.…”
Section: Receptive Languagementioning
confidence: 74%
“…Accordingly, children with severe autism may be more likely to display problems with directing their attention to social activities. In this study, as a result of the analysis of the corresponding subscale, the findings suggested that the children with severe autism demonstrated low levels of joint attention behaviors during their interactions with their mothers; in general, initiating joint attention and responding to joint attention bids have been found to be inadequate in children with autism (Mundy, 1995;Murray et al, 2008). However, when joint attention problems were considered as one of the distinguishing characteristics of children with autism in comparison to typically developing children or children with language and developmental disabilities (Schertz and Odom, 2004), one can assume that this finding is expected in the line of this study.…”
Section: Discussionmentioning
confidence: 96%